Penerapan Fungsi Gereja Berdasarkan Kisah Para Rasul 2:42-47 Di Masa Pandemi - Katarina Katarina; Sabda Budiman (Shalom: Jurnal Teologi Kristen, 2021)
The covid-19 pandemic is still sweeping the world today. The impact of this pandemic is also felt by the church so that the church is difficult to carry out its functions as a whole. The living church is the one that performs its functions. The early Church became a very good standard and example. This article formulates the problem of how the church functions based on Acts 2:42-47 during the pandemic? The purpose of this writing is to explain the application of the functions of the church in Acts 2:42-47 during the pandemic. The research method used in this study is qualitative research with library study approach which is the hermeneutic method of the Bible. The results of this study show that there are five functions of the church based on Acts 2:42-47, namely fellowship, discipleship, devotion, evangelism, and worship. In implementing these five church functions in the current pandemic situation, there are two applications, namely internal application that discusses building relationships with God and others, and internal application that includes community service and evangelism.